STUDY OF THE BIOLOGICAL PROPERTIES OF THE NEWCASTLE DISEASE VIRUS STRAINS - Nurkhojayev, N.; Assanov, N.; Mussina, G.; Mussoev, A. (Ғылым және білім №1, 2020)
Newcastle disease is the most contagious and dangerous viral infection of domestic and wild birds. Kazakhstan has a huge territory crossed by large overpasses, and hundreds of bird species are concentrated in natural landscapes during periods of migration and reproduction The data obtained in many years of research indicate a poor situation in Kazakhstan due to Newcastle disease among domestic birds of both industrial and household content. Circulation in populations of synanthropic birds epizotically topical, mesogenic strains the virus of Newcastle disease, which antigenetically differs from previously circulating variants, determines the need for regular monitoring of this pathogen to Kazakhstan From the scientific data it should be emphasized that the most significant viral infection for the poultry industry of the Republic of Kazakhstan, Newcastle disease continues to be in sight, leading positions in terms of the degree of danger and economic losses. The analysis of the spread of these diseases in the Republic of Kazakhstan is characterized by the annual registration of new foci of diseases. Болезнь Ньюкасла является наиболее контагиозным и опасным вирусным инфекцием домашних и диких птиц. Казахстан имеет огромную территорию, пересекаемую большими пролетными путями, и сотни видов птиц концентрируются в природных ландшафтах в периоды миграции и размножения. Полученные в ходе многолетних исследований данные свидетельствуют о неблагополучной обстановке в Казахстане по болезни Ньюкасла среди домашних птиц как промышленного, так и приусадебного содержания. Циркуляция в популяциях синантропных птиц эпизоотически актуальных, мезогенных штаммов вирус болезни ньюкасла антигенно отличающихся от ранее циркулировавших вариантов, определяет необходимость проведения регулярного мониторинга этого возбудителя в Казахстане. Из научных данных следует подчеркнуть, что наиболее значимые для птицеводства Республики Казахстан вирусная инфекция болезнь Ньюкасла продолжает оставаться на виду, занимая лидирующие позиции по степени опасности и экономических потерь. Анализ распространения этих болезней в Республике Казахстан характеризуется ежегодной регистрацией новых очагов болезней. В данной статье приведены результаты исследовании биологических свойств двух штаммов вируса болезни Ньюкасла, изолированных от кур содержащегося в частном подворье и одного вируса изолированных от павшего голубя на террритории города Алматы.
Keywords: ветеринария; болезнь ньюкасла; птицеводство; болезнь птиц; newcastle’s disease; type 1 paramyxovirus of birds; genotype; рк